Social responsibility and its impact: A methodological proposal - Rosa, M. V.; Bacelar-Nicolau, L.; Ferreiro, M. de F. (Methodological Innovations, 2025)
Social responsibility has emerged as one of the predominant topics in public discourse since the beginning of the century, not only at the level of social organizations but also within corporate spheres. Since the 1990s, many methods have been developed to measure social impact, showing the extent to which there is a need to evaluate this complex and multidimensional reality. However, despite these multiple efforts, none of these methodologies has become a reference standard. An exhaustive literature review was conducted to carry out a classification of SIA models, aimed at understanding their strengths and weaknesses, as well as identifying any gaps within the sector. The work encompassed both mapping and classifying SIA models along with identifying indicators related to these models. Later, efforts were made to harmonize indicator nomenclature through a combination of manual and automated methods. 144 methodologies and 1361 indicators were listed. First, the study concluded that there is no universally accepted definition of the concept of Social Impact. Second, the study concluded that no existing measurement fully meets the three fundamental characteristics outlined in the literature: producing a quantitative output, being exhaustive (i.e., considering all stakeholders), and enabling comparability over time and across (social and business) organizations or projects with differing characteristics.